2017
DOI: 10.1002/tcr.201600138
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fischer Indolization under Green Conditions using Deep Eutectic Solvents

Abstract: Indole and its derivatives captured the attention of organic chemists due to their applications in medicinal chemistry. The examples covered here are intricate polycyclic indole derivatives and these include: azapolyquinanes, cyclophanes, spirocycles and other heterocycles. We found that deep eutectic mixture such as L-(+)-tartaric acid (TA) and dimethyl urea (DMU) is useful to prepare complex unnatural indole derivatives. These conditions from time to time produced indole derivatives which are not possible by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…In view of our interest in the design of indole-based azapolyquinanes, 14 we found that endo-DCPD could be used as a useful synthon to generate aza-polyquinanes by employing Fischer indolization (FI) and RRM as key steps. 12a To expand the strategy, we envisioned that the exo-DCPD may be a worthy candidate to synthesize fused hetero-polycyclics/fused medium-ring-containing aza-polyquinanes.…”
Section: Paper Syn Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…In view of our interest in the design of indole-based azapolyquinanes, 14 we found that endo-DCPD could be used as a useful synthon to generate aza-polyquinanes by employing Fischer indolization (FI) and RRM as key steps. 12a To expand the strategy, we envisioned that the exo-DCPD may be a worthy candidate to synthesize fused hetero-polycyclics/fused medium-ring-containing aza-polyquinanes.…”
Section: Paper Syn Thesismentioning
confidence: 99%
“…15,16 Enone 13 was then subjected to Zn-AcOH mediated reduction to afford the saturated ketone 14 in 87% yield. 17 Next, the tricyclic exo-ketone 14 was subjected to FI 14,18 by reaction with phenylhydrazine hydrochloride 15 in a low-melting mixture of L-(+)-tartaric acid (TA) and N,N′-dimethylurea (N,N′-DMU) at 90-100 °C to give indole derivative 12 in 95% yield. With indole derivative 12 in hand, initially it was subjected to an N-allylation and N-propargylation sequence separately in the presence of NaH in anhydrous DMF at 0 °C to deliver the corresponding N-substituted aza-polyquinanes 16 and 17 in good yields (Scheme 1).…”
Section: Paper Syn Thesismentioning
confidence: 99%
“…[25] The reactivity profile of indole is particularly interesting for synthetic chemists, since it is vulnerable to electrophilic aromatic substitution, hydrogenation, cycloaddition and oxidation, while its amine lone pair is unavailable due to aromaticity, whereas the NÀ H proton is acidic. [26] Indeed, there are numerous studies of reactions of indole-type compounds in DES, [27] for example, ultrasound synthesis of 3-substituted indoles, [28] Fischer indolization in DES, [29] and simple [27] and Friedel-Crafts alkylations. [30] Thus, we consider indole to be an interesting proxy molecule, both for the solvation of metabolites in deep eutectic solvents made from potentially naturallysourced components, and for the solvation of small-molecule organic reaction precursors, in reactions involving indole itself and similar heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48] These NADES are obtained via the complexation between hydrogen bond donors and hydrogen bond acceptors and like usual DES, they also exhibit some interesting properties such as low-volatility, renewable, non-toxic, biodegradable, reusable, inexpensive, atom economical, bio-compatible, thermally stable, water-compatible, inflammable, playing a double or triple role (solvent, catalyst and/or reactant) during the chemical transformation. [49][50][51][52][53][54][55][56][57][58][59] Keeping these interesting properties in mind, we became interested in deciphering the role of DESs in general and NADES in particular for the condensation reaction of various aromatic aldehydes and amides to assemble a library of symmetrical bisamides.…”
Section: Introductionmentioning
confidence: 99%